Immediate Results of Colonic Flat Epithelial Neoplasms Removal Using Diathermic Snare Endoscopic Mucosal Resection and Mucosectomy Combined with Dissection in the Submucosal Layer: Comparative Assessment - A. A. Fedorenko; P. V. Pavlov; A. P. Kiryukhin; A. S. Tertychnyy (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to compare the immediate outcomes of removing colonic flat epithelial neoplasms by using diathermic snare endoscopic mucosal resection (EMR) and mucosectomy with endoscopic submucosal dissection (ESD).Materials and methods. Ninety-six endoscopic procedures were conducted on the colon of 93 patients with flat epithelial neoplasms. The mean age of patients was 64.9 ± 10.7 years, with an age range of 39 to 88 years. The size range of epithelial neoplasms was 20 to 70 mm, with a median of 37.4 ± 14.8 mm. Only patients with benign epithelial neoplasms were included in the study since patients with suspected malignancy in laterally spreading tumors are indicated for ESD intervention to avoid fragmentary excision and risk of colorectal cancer progression due to possible positive resection margins. The patients were separated into two equally sized groups and treated with EMR and ESD methods.Results. Epithelial neoplasms in the ESD group had an average size of 41.6 ± 15 mm while those in the EMR group had an average size of 33.1 ± 13.5 mm. The ESD group had an average intervention time of 143.6 ± 102.9 min, whereas the EMR group had an average intervention time of 52.6 ± 34.4 min. Both groups (96 adenomas) had a total of 10 (10.4 %) patients who experienced colonic perforations during the intervention, with 4 (4.1 %) cases observed in the EMR group and 6 (6.2 %) in the ESD group. No statistically significant differences were identified in the occurrence of perforations during the operation (p = 0.7401). ESD resulted in an en bloc removal rate of 44/48 (91.6 %), whereas EMR only achieved a rate of 14/48 (29.1 %).Conclusion. Endoscopic mucosectomy with submucosal dissection (ESD), in contrast to endoscopic mucosal resection (EMR) with diathermic snare, provides a higher frequency of tumor removal en bloc, regardless of tumor size, but is characterized by a longer duration of intervention (p < 0.0001). In the ESD group, there were twice as many intraoperative bleedings (p = 0.0061) due to the longer duration and technical complexity of the procedure. There were no statistically significant differences in the incidence of late complications between the groups (p = 0.9999). Local recurrence of adenoma developed in two patients (4.1 %) after pEMR, statistically significant differences were noted (p < 0.0006).